2005 European Microwave Conference 2005
DOI: 10.1109/eumc.2005.1610104
|View full text |Cite
|
Sign up to set email alerts
|

Low-loss bandpass antenna-filter-antenna arrays for applications in quasi-optical systems

Abstract: __ A new type of 3-pole frequency selective surface (FSS) is proposed as a low-loss bandpass filter for Quasi-Optical applications. This FSS is realized as a uniform array of antenna-filter-antenna (AFA) elements. Each AFA element is a three layer structure consisting two slot antennas and a stripline resonator. A Chebyshev bandpass AFA with 9.5% bandwidth was designed for 32 GHz and fabricated on two layers of Teflon substrates ( r =2.2, tan =0.0009). The maximum measured in-band insertion loss for this desig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…To enable a quantitative evaluation of the proposed topology, we consider a LEPA configuration where the PA is implemented as an array of x-directed electric dipoles and the LA is implemented as an array of slot-based antenna-filter-antenna (AFA) elements [12,13], with y-directed slot antennas on the side facing PA and x-directed slot antennas on the opposite side.…”
Section: Analysis Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To enable a quantitative evaluation of the proposed topology, we consider a LEPA configuration where the PA is implemented as an array of x-directed electric dipoles and the LA is implemented as an array of slot-based antenna-filter-antenna (AFA) elements [12,13], with y-directed slot antennas on the side facing PA and x-directed slot antennas on the opposite side.…”
Section: Analysis Methodsmentioning
confidence: 99%
“…For analysis, Friis' formula and geometric distance between AFA elements and the feed antenna are used to calculate the complex amplitude of the incident wave at the input of each AFA cell and the simulated element transmission coefficients are utilized to reconstruct the aperture distribution over the output side of the LA and, in turn, the far field. For simple feed and LA systems, it has been shown that this hybrid analysis method produces accurate predictions of the overall gain and radiation pattern for observation angles within the main lobe and first two sidelobes [13]. In the case of LEPA, where the distance between LA and PA can be much smaller, the method can be modified by using a Green's function calculation instead of Friis' formula to find the input amplitude for each AFA element.…”
Section: Analysis Methodsmentioning
confidence: 99%
“…The advantage of utilizing slot antennas is their potential to result in very low-loss arrays [19]. The slot lengths are designed for resonance at the center of the operation band and the slot widths are adjusted for the required value of radiation bandwidth (equivalent to of the filter).…”
Section: B Design Methods and Circuit Modelmentioning
confidence: 99%